An appeal to the people: politeness strategies in the Malaysian prime minister's maiden speech / Nadia Anuar and Nurizah Md Ngadiran - Anuar, Nadia; Md Ngadiran, Nurizah (Universiti Teknologi MARA, 2021)
The use of politeness strategies has received increasing attention in the political discourse as a powerful persuasion tool. These strategies became critical for the newly appointed prime minister of Malaysia, Tan Sri Muhyiddin Yassin, to convince Malaysians that he is qualified to lead the country during political upheaval and global pandemic. Thus, the objectives of this paper are to identify the types and frequency of the politeness strategies used by Muhyiddin Yassin in his maiden speech as the eighth prime minister of Malaysia. Two categories of politeness strategies based on Brown and Levinson's (1987) were examined, which are negative strategies and positive strategies. The speech text was obtained from the official website of Prime Minister's Office and was translated to English for analysis. The translated speech was subsequently checked for validity. Document analysis was used to analyse the translated speech text to determine the types and frequency of the politeness strategies. The analysis revealed that positive politeness strategies were significantly used (88%) compared to negative politeness strategies (12%). The most dominantly used positive politeness strategy was "notice and attend to the receiver's need, interest, or want" while "use of exaggeration", "seek agreement", and "avoid disagreement" were the least used strategies. In contrast, "question" and "giving deference" were identified to be the most frequently used negative politeness strategies. The present study extends our knowledge on the use of politeness strategies in a political speech in an Asian setting, which is notably lacking in the literature.